RETRACTED: Yield and physical pulp properties of three Eucalyptus Pellita F. Muell clones at two active alkali concentrations: A study in tropical agriculture practices - Adi, Rian Palimirmo; Marsoem, Sri Nugroho; Lukmandaru, Ganis (Holistic: Journal of Tropical Agriculture Sciences, 2025)
Background: Efforts to enhance the genetic quality of Eucalyptus pellita F. Muell by PT. Riau Andalan Pulp and Paper included breeding several clones to optimize raw materials for pulp and paper production. Three clones—CEP06, CEP13, and CGP32—were selected to determine their potential based on pulp yield and physical properties. Methods: The wood samples from these clones were cooked using the sulfate process with active alkali concentrations of 13% and 15%, 25% sulfidity, a wood-to-liquor ratio of 1:4, a cooking temperature of 170°C, and a cooking duration of 2 hours. Pulp yields, kappa numbers, and pulp properties, including tear, burst, and tensile indices, were analyzed. Statistical analysis employed Analysis of Variance (ANOVA) and Honestly Significant Difference (HSD) tests. Findings: The clones CEP13 and CGP32 achieved higher screened yields at 38.34% and 38.26%, respectively, compared to CEP06. However, CEP06 demonstrated superior tear and burst indices of 6.36 mN·m²/g and 3.60 kPa·m²/g, respectively. The highest tensile index of 41.75 Nm/g was observed in the CGP32 clone. Significant differences were found among the clones in terms of screened yield, kappa number, and certain pulp properties. Additionally, active alkali concentrations significantly affected the screened yield and kappa number, with interactions between clones and alkali concentrations significantly influencing kappa numbers. Conclusion: The CEP06 clone is recommended for pulp and paper production due to its favorable pulp properties, making it an excellent raw material candidate. Novelty/Originality of this article: This study highlights the potential of Eucalyptus pellita clones in optimizing raw materials for pulp and paper industries, emphasizing their specific advantages and contributions to sustainable forestry practices.